Gromadkarstwo – ruch religijno-społeczny w Prusach Wschodnich - Warda, Elwira (Archiwa, Biblioteki i Muzea Kościelne, 2018)
In East Prussia, the revival movement (Erweckungsbewegung) was formed by the eighteenth-century pietist school of the University of Königsberg. The development of the pietist movement in Prussia was influenced by the Brethren’s Congregation from Herrnhut (the Unity of the Brethren) and so-called the Brethren from Salzburg. The movement of the Brethren from Salzburg gave a direct impetus to the creation of the movement called Gromadkarstwo. In the 19th century, this movement was formed as an opposition to the official Church, and its members also participated in their own congregations led by lay people. There were various reasons for the development of Gromadkarstwo. By the middle of the 19th century, Gromadkarstwo in East Prussia had been purely folk in character, and its members did not leave virtually any documents. Peasants became nomadic preachers, spreading the gospel from village to village. It was only after 1885 that the mass movement became organized and institutionalized. In the Lutheran Church in East Prussia, it survived until the Second World War.